Applications of 3D printing technologies in oceanography - Javeed Shaikh, Mohammed (Elsevier, 2016)
3D printers allow researchers to produce parts and concept models rapidly at low-cost and allow rapid prototyping of many designs from the comfort of their desk. 3D printing technologies have been explored for a wide range of applications including robotics, automobile components, firearms, medicine, space, etc. Owing to lower costs and increased capabilities of 3D printing technologies, unprecedented opportunities in the world of oceanography research are being created. Some examples include 3D printed components being employed in autonomous underwater (or surface) vehicles; 3D printed replicas of marine organisms being used to study biomechanics, hydrodynamics, and locomotion; and 3D printed coral reef replicas being used to restore damaged coral reefs. To the author's knowledge, currently there is no review covering the different 3D printing technologies applied in oceanography studies. Therefore, this review presents a summary of the different 3D printing technologies that have been used in fundamental studies or real-life applications related to oceanography. The diverse range of 3D printing applications in oceanography covered in this review has been categorized under the following sub-topics: Ecological Monitoring & Sample Collection, Hydrodynamics, Biomechanics & Locomotion, Tracking & Surface Studies, and Tangible Coral Props & Coral Reef Restoration. A detailed overview of the 3D printing technologies referred to within this review has been presented, and categorized under the following four general topics: Material Extrusion, Photopolymerization, Powder Bed Fusion, and Construction Printing. The broad impact of plastics on oceans and the specific impact of 3D printing materials on ocean life are also discussed. It is anticipated that this review will further promote the 3D printing technologies to oceanographers for a better understanding and restoration of fragile marine ecosystems.